An An Analysis of Strain Rate Distribution Using Streamline Model and A Quick Stop Device in Metal Cutting - Kadhim, Osama Ali; Alshamma, Fathi A. (Al-Nahrain Journal for Engineering Sciences, 2019)
In this paper, a quick stop device technique and the streamline model were employed to study the chip formation in metal cutting. The behavior of chip deformation at the primary shear zone was described by this model. Orthogonal test of turning process over a workpiece of the 6061-T6 aluminum alloy at different cutting speeds was carried out. The results of the equivalent strain rate and cumulative plastic strain were used to describe the complexity of chip formation. Finite element analysis by ABAQUS/explicit package was also employed to verify the streamline model. Some behavior of formation and strain rate distribution differs from the experimental results, but the overall trend and maximum results are approximately close. In addition, the quick stop device technique is described in detail. Which could be used in other kinds of studies, such as the metallurgical observation.